Somewhere in time [videorecording (DVD)] - Szwarc, Jeannot, 1939-; Reeve, Christopher, 1952-2004; Seymour, Jane, 1951-; Plummer, Christopher; Matheson, Richard, 1926-2013 (Universal Studios Home Video, 2000)
A young writer sacrifices his life in the present to find happiness with a beautiful woman in the past.